Patient-derived primary breast cancer cells and their potential for predicting sensitivity to chemotherapy - Mou, Yajun; Huang, Jianjun; Yang, Wenxiu; Wan, Yu; Pu, Zhenhong; Zhang, Junhong; Liu, Jinting; Li, Qing; Zhang, Peipei; Tian, Yuan; Yang, Hui; Cui, Yi; et al. (Frontiers in Oncology, 2022)
Chemotherapy resistance exposes patients to side effects and delays the effect of therapy in patients. So far, there are no predictive tools to predict resistance to chemotherapy and select sensitive chemotherapeutic drugs for the patient. Here, we aim to develop an in-vitro primary cell culture model from breast cancer patients to predict sensitivity to chemotherapy. We created the primary breast cancer cell medium BCMI and culture system with higher efficiency of the model establishment. Immunofluorescence staining of ERa, PR and HER2 were done to identify the primary breast cancer cell from the counterpart breast cancer patient. The killing assay showed that these primary breast cancer cells responded differently to doxorubicin and pirarubicin treatment. These results indicate that our established primary breast cancer cell model holds great promise for predicting breast cancer sensitivity to chemotherapy drugs.